(untitled) (Biological Sciences - PJSIR, 2004)
Food legumes, widely grown and consumed throughout the world are excellent sources of proteins (20 - 25%) and carbo- hydrates (50 - 60%). They are also fairly good sources of dietary fibre, minerals and vitamins. However, presence of tannins, phytic acid and other anti-nutritional substances re- duce the availability of protein and other nutrients in legumes